Influence of the substituents on phenyl groups on enantioseparation property of amylose phenylcarbamates. (1st August 2020) - Bi, Wanying; Wang, Fan; Han, Jinhang; Liu, Bo; Shen, Jun; Zhang, Lili; Okamoto, Yoshio
Highlights: Five amylose phenylcarbamates with various substituents on phenyl moieties. Influence of substituent on chiral recognition of amylose derivatives. Relationship between structure and enantioseparation property of amylose derivatives. 3-Chloro-5-methyl and 3, 5-dimethylphenylcarbamate showed higher recognition ability. Substituent-dependent conformation change was demonstrated by molecular docking. Abstract: A series of amylose phenylcarbamate derivatives bearing different chloro- or/and methyl- substituents on the phenyl groups were synthesized and their enantioseparation properties were examined by high-performance liquid chromatography. The enantioseparation power considerably altered due to the substituents on the phenyl units. The amylose derivative bearing 3-chloro-5-methyl disubstituents seemed to possess much higher chiral resolution power. The introduction of both an electron-withdrawing chloro and an electron-donating methyl groups enabled the NH groups to contain a moderate acidity, which may be important to construct a regular secondary structure for the amylose phenylcarbamates. Some interesting observations in 1 H NMR and circular dichroism spectroscopy demonstrated the correlations between the structure and enantioseparation ability. The electronegativity, location and amount of the substituents at the phenyl residues have great influence on the enantioseparation power of the amylose derivatives. The mechanism involved in enantioselective discrimination of the amylose phenylcarbamates was further investigated by the molecular docking simulation.